Extraction and characterization of nanocellulose crystals from cotton gin motes and cotton gin waste - Jordan, Jacobs H.; Easson, Michael W.; Dien, Bruce; Thompson, Stephanie; Condon, Brian D. (Cellulose (London), 2019)
Cellulose nanocrystals (CNC) have attracted a great deal of attention as an environmentally-friendly biorenewable resource for use as reinforcing agents in nanocomposites, polymers, gels, and emulsions. CNCs are typically prepared from extracted cellulose or highly refined cellulose products. The chemical refining process can alter the chemical and physical properties of the cellulose fibers prior to extraction of CNCs. Moreover, the method of isolation can also insert various functional groups onto the nanocellulose, affecting thermal stability and imparting different physical properties. Herein, two byproducts of the cotton industry, cotton gin motes and cotton gin waste, are investigated for the preparation of nanocelluloses. Cellulose was purified from these two post-process agroindustrial by-products and CNCs subsequently produced by sulfuric acid hydrolysis. Additionally, two acid hydrolysis methods were utilized to successfully extract CNCs from gin motes without chemical pretreatment. CNCs were obtained with diameters < 10 nm and lengths of ca. 100–300 nm resulting in high aspect ratios (12–33). Incorporating CNCs with these dimensions impart increased hydrophilicity to a substrate. The effect of post-extraction chemical treatments on crystallinity and morphology are discussed. The extracted nanocellulose derivatives were additionally characterized by FTIR, AFM, TGA, DLS, XRD and XPS. Differences in extraction method and chemical treatment resulted in different thermal properties and colloidal stability. Furthermore, this work provides a means of producing a high value commodity from inexpensive source materials such as cotton gin motes and cotton gin waste.